Inflación y rendimientos en mercados emergentes: El caso de Argentina; Inflation and returns in emerging markets: The case of Argentina - Gabriela Pesce; Florencia Verónica Pedroni (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2021)
– This paper aims to carry out a preliminary analysis of the arbitrage pricing theory in Argentine capital market, with special emphasis on inflation as a variable of interest for an emerging country, an underdeveloped financial market, and a period under analysis with inflationary trends and exchange market intervention. To that end, we work with a theoretical-empirical method. In order to formulate the model, we make a theoretical approach to the subject, based mainly on scientific articles that examine the relationship between the rate of return on assets and inflation. We focus our empirical analysis in an econometric study of the shares' performance of 19 companies listed on Argentinian capital market in the 2005-2014 period, and the associations with variables of interest, especially macroeconomic ones, also including some control tests with microeconomic variables. The main findings are robust about the effect on firms' performance of the following explanatory variables: risk-free interest rate, market performance, temporary effects of 'hinge' periods and sector effects. However, the results are not determinant in reference to the effect of the inflation and the exchange rate variables on stocks' performance.
Keywords: E31; E44; G32; O16; 330; yield; inflation; panel data; arbitrage pricing theory